The T4 Phage DNA Mimic Protein Arn Inhibits the DNA Binding Activity of the Bacterial Histone-like Protein H-NS - Ho, Chun-Han (American Society for Biochemistry and Molecular Biology, 2014)
The T4 phage protein Arn (Anti restriction nuclease) was identified as an inhibitor of the restriction enzyme McrBC. However, until now its molecular mechanism remained unclear. In the present study we used structural approaches to investigate biological properties of Arn. A structural analysis of Arn revealed that its shape and negative charge distribution are similar to dsDNA, suggesting that this protein could act as a DNA mimic. In a subsequent proteomic analysis, we found that the bacterial histone-like protein H-NS interacts with Arn, implying a new function. An electrophoretic mobility shift assay showed that Arn prevents H-NS from binding to the Escherichia coli hns and T4 p8.1 promoters. In vitro gene expression and electron microscopy analyses also indicated that Arn counteracts the gene-silencing effect of H-NS on a reporter gene. Because McrBC and H-NS both participate in the host defense system, our findings suggest that T4 Arn might knock down these mechanisms using its DNA mimicking properties.